Fishing during extreme heatwaves alters ecological interactions and increases indirect fishing mortality in a ubiquitous nearshore system - Jeff C. Clements; Sarah Harrison; Mylène Roussel; Jillian Hunt; Brooke-Lyn Power; Rémi Sonier (Communications Biology)
Abstract Heatwaves may have multifaceted ecological impacts; however, field studies assessing the ecological ramifications of nearshore fishing during heatwaves are rare. We leverage a field experiment simulating clam fishing to document such effects on a ubiquitous ecological system at the land-sea interface. During monthly field trials from May-September 2024, we experimentally fished clams at low tide and tracked reburrowing and mortality rates of marked, sub-legal sized clams returned to the sediment. Half of the clams were protected from crab predation and estimates of predator and scavenger activity were recorded. Clams typically reburrowed quickly and mortality was low. During the heatwave, however, clams appeared unhealthy, failed to reburrow, and suffered near-complete mortality. Predator activity in experimental plots was >4× higher during the heatwave compared to other months. Clam mortality during the heatwave was likely a combined result of physiological death and increased predation. When put into the context of air temperature during fishing, there was a clear ecological shift at 30 °C, whereby clam reburrowing plummeted, and predator/scavenger activity and clam mortality dramatically increased. These results provide in situ documentation of human-climate interactions influencing indirect fishing mortality and altering ecological dynamics, ultimately generating pertinent information for ecosystem-based fisheries management.